Ibadah Puasa Ramadhan dalam Perspektif Islam dan Kesehatan - Firdaus Firdaus; Tati Yalina Andiyah; Lidya Andita; Saras Ainurrochimah; Fajrul Hakim; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islam considers that health is part of Allah's greatest favor. Medically, fasting can cleanse toxins and substances that accumulate in the digestive tract, kidneys, and other organs of the body due to preservatives, dyes, artificial sweeteners, cancer-causing carcinogenic substances, cigarette smoke and others that accumulate over the years. Although our body's mechanisms have the ability to treat themselves, the body's capacity also has its limits. By fasting, the protection of the body's organs can be perfect. The purpose of this research is to inform Muslims that fasting is mandatory for us to carry it out. In the Qur'an, surah al-Baqarah 2:183. Allah SWT said,